Timsko delo knjižničarja na dveh delovnih mestih in izgorelost - Jesih Šterbenc, Katarina (Šolska knjižnica, 2016)
The paper presents the personal experience of a school librarian working in two institutions. It presents the positive and negative experiences of such employment, the stressful situations connected with it, and the process of resolving them. A stressful situation occurred when the school library underwent a change in personnel. The retirement of an older librarian and the arrival of a fellow teacher was an additional stress factor. The paper's author remained in the library as a part-time librarian, who is additionally working at another school. The conditions which had been created in the school library presented a challenge to the librarian's personal growth, the improvement of the school climate, and the reorganisation of work in the library. Cooperation with her co-workers deepened, new social networks were formed, and stress factors became manageable. Despite the increasing workload, the experiences gained by the librarian from working in two institutions are invaluable.
Keywords: izgorelost; srednje šole; stres; šolska knjižnica; šolski knjižničarji